To catch a cheat - Johnson, Varian; Johnson, Varian (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
Because of his reputation for practical jokes Jackson Greene is the automatic suspect for anything that goes wrong at school--but when he and his friends are framed for a crime they did not commit, Gang Greene sets out to expose the students responsible, who are trying to blackmail Jackson into helping them cheat on an important test.
Sequel to: The great greene heist.
School Library Journal, December 2015
Kirkus Starred, October 2015
Horn Book, January 2016
4.2
3-6
Keywords: Cheating (Education) -- Juvenile fiction; Extortion -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; African Americans -- Juvenile fiction; Cheating -- Fiction; Extortion -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Cheating (Education) -- Fiction; Extortion -- Fiction; Middle schools -- Fiction; School stories; Friendship -- Fiction; African Americans -- Fiction